Nutrient content of Liquid Organic Fertilizer (LOF) by various bioactivator and soaking time - INCE RADEN; S. SYARIEF FATHILLAH; M. FADLI; SUYADI SUYADI (Nusantara Bioscience, 2017)
Raden I, Fathillah SS, Fadli M, Suyadi. 2017. Nutrient content of Liquid Organic Fertilizer (LOF) by various bio-activator and soaking time. Nusantara Bioscience 9: 209-213. Inorganic fertilizers have negative impacts on soil structure, cause water and soil pollution, and produce less healthy crop production. These conditions can be improved with organic fertilizers. The research aimed to make liquid organic fertilizer (LOF) treated with various bio-activator and soaking time and to know the nutritional content in it as well. Observed variables were pH; C/N ratio; macro and micro nutrients. Research used a completely randomized design in factorial analysis. The first factor was the various bio-activator (b), i.e. b1 = EM-4 culture; b2 = boisca; and b3 = shrimp paste. The second factor was soaking time (t), i.e. t1 = 10 days; t2 = 20 days, t3 = 30 days; and t4 = 40 days. The treatment was repeated (r) three times and tested by analysis of variance and LSD at 5% level. The results showed that culture of EM4 bio-activator had higher content of C/N ratio; organic-C; total-N; Co; B; Mn; Fe; Cu; and Zn than the other bio-activators, although it also had lower content of pH, P2O5; K2O than others but those values were not significantly different compared to boisca and shrimp paste bio-activators. The other result showed that soaking time had significantly effect in determining the nutrient content of the C/N ratio; Organic-C; Total-N; P2O5 ; K2O; Total-Ca; Mg; S; Co; B; Mn; Fe; Cu; and Zn, but not at pH variable. Soaking time of 40 days (t4) provided the highest value on the C/N ratio; pH; Mn; Fe; and Zn. On the other hand, soaking time of 30 days (t3) provided the highest value on the organic-C; K2O; total-Ca; and B. Meanwhile, soaking time of 20 days (t2) provided the highest nutrient values on Cu; Co; B; Mg; and total-N. While, soaking time of 10 days (t1) gave the highest value on the nutrient content of P2O5 and S. The interaction between the various bio-activator and soaking time b3t3 had the highest value 575.41 ppm of B, then treatment b2t3 had the highest 0.89% of K2O, and treatment b1t4 gave the highest nutrient content 1648.82 ppm of Fe.